Data warehouse model for mobile-based applications - Abu Bakar, Muhamad Shahbani; Ta'a, Azman (IJERA, 2016)
Analysis and design are very important roles in the Data Warehouse (DW) system development and forms as a backbone of any successful or failure of the DW project.The emerging trends of analytic-based application required the DW system to be implemented in the mobile environment. However, current analysis and design approaches are based on existing DW environments that focusing on the deployment of the DW system in traditional web-based applications.This will create the limitations on user accessed and the used of analytical information by the decision makers. Consequently, this will prolong the adoption of analytic-based applications to the users and organizations.This research aims to suggest an approach for modeling the DW and design the DW system on the mobile environments. A variant dimension of modeling techniques was used to enhance the DW schemas in order to accommodate the requirements of mobile characteristics in the DW design.A proposed mobile DW system was evaluated by expert review, and support the success of mobile DW-based application implementation.